Cyclophilin A causes severe fever with thrombocytopenia syndrome virus-induced cytokine storm by regulating mitogen-activated protein kinase pathway - Huang, Huaying; Jin, Ke; Ouyang, Ke; Jiang, Zhengyi; Yang, Zhan; Hu, Nannan; Dai, Yan; Zhang, Yaqin; Zhang, Qian; Han, Ying; Zhao, Jie; Lin, Hong; et al. (Frontiers in Microbiology, 2022)
Introduction Severe fever with thrombocytopenia syndrome (SFTS) has become a global threat to public health since its first report in China in 2009. However, the pathogenesis of SFTS virus (SFTSV) in humans remains unclear. Also, there are no effective therapeutics for SFTS. Cyclophilin A (CyPA) regulates protein folding and trafficking involved in various viral infectious diseases, but its role in SFTSV infection has not been elucidated. Methods We detected plasma CyPA levels in 29 healthy subjects and 30 SFTS patients by ELISA. In THP-1 cells and normal human peripheral blood mononuclear cells (PBMCs), SFTSV-induced extracellular CyPA (eCyPA) was also detected by ELISA. In THP-1, the effects of CyPA on Mitogen-activated protein kinase (MAPK) pathway and NF-κB were determined by Western blot. We validated the interaction between CypA and CD147 by human recombinant CyPA (hrCyPA) and the CD147 inhibitor. Effects of CyPA inhibitor Cyclosporine A (CsA) on cytokines and SFTSV replication in THP-1 cells was also detected. 8-week-old Interferon-α/β Receptor (IFNAR) knockout (IFNAR-/-) C57BL/6 mice were divided into mock group, 106TCID50 SFTSV (Untreated) group and 106TCID50 SFTSV+CsA (CsA-treated) group. The changes of body weight, animal behavior and survival time of each group were recorded. Blood samples were collected from tail vein regularly. After death, the liver, spleen, lung, kidney and brain were collected for pathological HE staining and SFTSV-NP immunohistochemical staining. Results Compared to healthy subjects and SFTS patients in the febrile phase of the disease, plasma CyPA levels in SFTS patients at the multi-organ dysfunction (MOD) phase showed significantly elevated (P < 0.01). Extracellular CyPA activates the MAPK pathway by binding to CD147 in THP-1 infected with SFTSV. CsA inhibits the pro-inflammatory and promoting replication effects of CyPA after SFTSV infection in vitro. In vivo, CsA can prolong the survival time and delay the weight loss of SFTSV mice. CsA reduces multi-organ dysfunction in IFNAR−/− mice infected with SFTSV. Discussion Our results indicate that CyPA is associated with SFTSV-induced cytokine storm, which can be a potential target for SFTS therapy.